Effects of wood ash, nitrogen, and biosolids fertilisation on the growth and soil properties of Scots pine and Norway spruce stands - Mäkinen, Harri; Ilvesniemi, Hannu; Lindroos, Antti-Jussi; Smolander, Aino (Elsevier, 2025)
The recycling of wood ash back to forests has the potential to restore nutrients that are removed during the harvesting of wood chips for bioenergy. Biosolids are nutrient-rich organic residual materials derived from biowaste and sewage sludge with potential use as fertiliser. The objective of this study was to assess the impact of wood ash fertilisation, with and without nitrogen (N) addition, as well as biosolids addition, on forest growth, and soil properties and processes. The material was collected from fertilisation experiments in southern Finland, two in Scots pine (Pinus sylvestris L.) stands and four in Norway spruce (Picea abies (L.) Karst.) stands on mineral soil, approximately 10 years after the treatments were applied. The treatments were as follows: a control with no fertilisation, two doses of wood ash (3000 kg ha−1, and 9000 kg ha−1), a nitrogen addition (180 kg ha−1), and treatments with N and ash additions. In addition, biosolids (4400 kg ha−1) were applied. The treatments had only a slight impact on growth in both pine and spruce stands. The most notable impact on the chemical properties of the humus layer was a reduction in acidity and an increase in base cation concentrations on the plots fertilised with ash. Conversely, the addition of N and/or wood ash did not result in a consistent impact on the C-to-N ratio, rates of carbon and net N mineralisation, or carbon and N amounts. The limited growth response to the N addition in any form is attributable to the minor alteration in N availability. Furthermore, the application of wood ash and biosolids did not result in any discernible adverse effects on soil properties.
Keywords: ash; biosolids; fertilisation; forest growth; nitrogen; soil properties